Broadband localized surface-plasmon-enhanced green light-emitting diodes by silver nanocone array. (28th October 2015) - Liu, Hao; Li, Yufeng; Huang, Yaping; Wang, Shuai; Feng, Lungang; Gong, Zhina; Wang, Jiangteng; Ding, Wen; Zhang, Ye; Yun, Feng
Abstract: Green light-emitting diodes (LEDs) with silver nanocone-shaped structures embedded in p-GaN have been demonstrated with the surface plasmon (SP) enhancement effect. The resonance frequency has been broadened and the strength of coupling has been considerably enhanced. Compared with the LED without Ag nanocones, the integrated photoluminescence (PL) intensity of the SP-enhanced LED was improved by ∼275%, and the electroluminescence (EL) enhancement ratio at a different wavelength was evaluated at an injection current of 50 mA/mm 2 . At the same time, a reduction in the recombination lifetime indicated an increased internal quantum efficiency of LEDs. The results of simulation using nanocones as well as nanorods indicate good correlation with the experimental observation of the broadening effect. This structure is promising for converting incident photons into the localized surface plasmon (LSP) mode, to enhance the emission of LEDs within a broad wavelength range.